2021
DOI: 10.1096/fj.202002072rr
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells from umbilical cord of women affected by gestational diabetes: A suitable in vitro model to study mechanisms of early vascular senescence in diabetes

Abstract: Human umbilical cord endothelial cells (HUVECs) obtained from women affected by gestational diabetes (GD‐HUVECs) display durable pro‐atherogenic modifications and might be considered a valid in vitro model for studying chronic hyperglycemia effects on early endothelial senescence. Here, we demonstrated that GD‐ compared to C‐HUVECs (controls) exhibited oxidative stress, altered both mitochondrial membrane potential and antioxidant response, significant increase of senescent cells characterized by a reduced NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 104 publications
2
16
0
Order By: Relevance
“…This leads to increased ROS-related endothelial dysfunction that is prevented by deacetylation of p66Shc (Kumar et al 2017 ). Moreover, a recent study showed that diabetic conditions negatively regulates antioxidant properties in endothelial cells and this effect was associated with acetylation of p53 and increased expression of p300 (Di Tomo et al 2021 ) These findings are in accordance with our results showing that elevated lysine acetylation is associated with dysfunctional VSMCs in diabetes. Given these findings, an approach that may effectively protect the vasculature from ROS insult is a treatment that prevents vascular hyperacetylation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This leads to increased ROS-related endothelial dysfunction that is prevented by deacetylation of p66Shc (Kumar et al 2017 ). Moreover, a recent study showed that diabetic conditions negatively regulates antioxidant properties in endothelial cells and this effect was associated with acetylation of p53 and increased expression of p300 (Di Tomo et al 2021 ) These findings are in accordance with our results showing that elevated lysine acetylation is associated with dysfunctional VSMCs in diabetes. Given these findings, an approach that may effectively protect the vasculature from ROS insult is a treatment that prevents vascular hyperacetylation.…”
Section: Discussionsupporting
confidence: 93%
“…Recent evidence has increasingly shown that glucose triggers post-translational modifications (PTM) in diabetes which may play an important role in the pathogenesis of diabetic cardiovascular complications (Mellor et al 2015 ; Di Tomo et al 2021 ; Zhang et al 2015 ). Among the PTMs, lysine acetylation, a reversible PTM that impacts protein activity, stability, and binding proteins, has recently been linked to cardiometabolic disorders such as obesity, metabolic syndrome, and cardiovascular diseases (Iyer et al 2012 ; Hu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells obtained in patients with diabetes exhibited a reduced SIRT-1 expression and increased p16, p21, and p53 activity. They postulated that those changes, together with p300 activation, induce persistent endothelial senescence in patients with GDM [ 177 ]. A microarray analysis revealed significant differences in the expression of numerous genes involved in cellular function and proliferation regulation in HUVECs collected from healthy controls and patients with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, diabetes-induced vascular dysfunction is epigenetically controlled by the fine balance of acetylation and deacetylation of transcription factors/regulators. Accumulated evidence reveals that acetyltransferase p300 plays a pivotal role in diabetes-induced accelerated cellular senescence and aging-related pathologies through alterations of different cellular programs [ 29 , 30 , 31 ]. It has been reported that the endothelial cells derived from gestational diabetes umbilical cord display accelerated senescence phenotype as evidenced by increased expression of senescence regulators including p16, p21, and p53 and senescence marker SA-β-Gal compared to control human umbilical vein endothelial cells (HUVECs).…”
Section: Acetyltransferase P300 In Cellular Senescence and Agingmentioning
confidence: 99%
“…It has been reported that the endothelial cells derived from gestational diabetes umbilical cord display accelerated senescence phenotype as evidenced by increased expression of senescence regulators including p16, p21, and p53 and senescence marker SA-β-Gal compared to control human umbilical vein endothelial cells (HUVECs). Interestingly, the levels of acetyltransferase p300 and acetylated p53 (K382) are significantly elevated in endothelial cells derived from a gestational diabetes umbilical cord compared to control, indicating the possible involvement of acetyltransferase p300 in diabetes-induced vascular endothelial senescence [ 29 ]. Furthermore, Mortuza and colleagues [ 30 ] demonstrated that vascular endothelial cells undergo senescence processes in response to high glucose, a pathological milieu of diabetic condition.…”
Section: Acetyltransferase P300 In Cellular Senescence and Agingmentioning
confidence: 99%